2022
DOI: 10.3389/fnut.2022.866239
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Antioxidant Properties of Germinated Soybean Protein Hydrolysates

Abstract: In this study, soybeans during different germination stages were described and compared with regard to morphology, water content, protein, amino acids, and isoflavones. The optimal conditions for the hydrolysis of proteins obtained from germinated soybeans were determined using the response surface methodology. Gel filtration chromatography was used to separate germinated soybean protein hydrolysates after ultrafiltration, whereas 2,2-Diphenyl-1-picrylhydrazyl (DPPH), ABTS•+, and FRAP assays were used to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
1
0
1
Order By: Relevance
“…Among them, peptides FPKYPVEPF ( 47 ), and HLPLPLLQSWM ( 48 ) had been identified as antioxidant peptides by different researchers. Antioxidant peptides isolated from soybean hydrolysate and egg white hydrolysate have also been reported to be attributed to histidine due to the protons providing the ability of the imidazole moiety ( 49 ). It has also been reported that the antioxidant activity of peptides in β-casein trypsin hydrolysates VKEAMAPK is derived from methionine ( 50 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among them, peptides FPKYPVEPF ( 47 ), and HLPLPLLQSWM ( 48 ) had been identified as antioxidant peptides by different researchers. Antioxidant peptides isolated from soybean hydrolysate and egg white hydrolysate have also been reported to be attributed to histidine due to the protons providing the ability of the imidazole moiety ( 49 ). It has also been reported that the antioxidant activity of peptides in β-casein trypsin hydrolysates VKEAMAPK is derived from methionine ( 50 ).…”
Section: Resultsmentioning
confidence: 99%
“…Soya fasulyesi yüksek miktarda protein (%40-50 (w/w)) içeriğine sahiptir [94]. Soya fasulyesi proteinleri, özellikle histidin, izolösin, lösin, fenilalanin, treonin ve triptofan gibi temel aminoasitlerin kaynağıdır [93].…”
Section: Soya Fasulyesiunclassified